The adverse effect of metabolic syndrome on left ventricular global strains and myocardial energetic efficiency in non-ischemic dilated cardiomyopathy patients: a cardiac magnetic resonance study - Meng-Ting Shen; Yuan Li; Ke Shi; Jin Wang; Li Jiang; Yu Jiang; Yue Gao; Shi-Qin Yu; Xue-Ming Li; Wei-Feng Yan; Zhi-Gang Yang (Cardiovascular Diabetology)
Abstract Background Metabolic syndrome (MetS) is a known risk factor for cardiovascular dysfunction; however, its impact on left ventricular (LV) global strains and myocardial energetic efficiency in non-ischemic dilated cardiomyopathy (NIDCM) remains inadequately understood. This study aimed to investigate the effect of MetS on LV dysfunction in NIDCM patients using cardiovascular magnetic resonance (CMR) imaging. Methods A total of 557 NIDCM patients (378 without MetS and 179 with MetS) who underwent CMR examination were included. CMR-derived LV strains, remodeling index (LVRI), global function index (LVGFI), and indexed myocardial energetic efficiency (MEEI) were assessed and compared between the groups. The independent determinants of LV global longitudinal peak strain (GLPS), LVRI, LVGFI, and MEEI were evaluated using multivariable linear regression analyses. Results Compared to NIDCM patients without MetS, those with MetS had significantly lower LVSVI, LVEF, and LVGFI, along with higher LVMI and LVRI (all p < 0.05). However, no significant differences were found in LVEDVI and LVESVI (both p > 0.05). In terms of LV strain, the NIDCM(MetS+) group exhibited worse global peak strain and peak diastolic strain rate in all three directions, as well as decreased radial and longitudinal peak systolic strain rate (PSSR) compared to the NIDCM (MetS−) group (all p < 0.05), while circumferential PSSR did not differ significantly (p > 0.05). The MEEI was significantly lower in the NIDCM(MetS+) group compared to the NIDCM(MetS−) group (0.30 [0.20, 0.45] ml/s/g vs. 0.39 [0.25, 0.58] ml/s/g, p < 0.001). Multivariable analysis identified the presence of MetS as an independent determinant of LV GLPS (β = 0.211, p < 0.001), LVRI (β = 0.147, p = 0.003), and MEEI (β = − 0.160, p < 0.001). Conclusion The presence of MetS worsens LV function, remodeling, and myocardial energetic efficiency in patients with NIDCM, as evidenced by declines in LV strain, global function parameters, and indexed myocardial energetic efficiency. These findings suggest that addressing metabolic abnormalities may be crucial for improving LV function and outcomes for patients with NIDCM.